1996
DOI: 10.1128/aac.40.12.2727
|View full text |Cite
|
Sign up to set email alerts
|

New pharmacokinetic in vitro model for studies of antibiotic activity against intracellular microorganisms

Abstract: The capacity for intracellular growth is an important survival strategy for a large group of common pathogens. Helicobacter pylori, the etiological agent for gastritis and duodenal ulcer, has been shown by both in vivo and in vitro studies to have the capacity to invade epithelial cells. In vitro models are used to study the effect of antibiotics on microoganisms. Most investigations are performed in broth culture or on agar plates, but kinetic models for bacteria in broth have been described. We present a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Culture plates were divided into four sectors: the first contained only the culture medium (blank), the second 8 mg/L metronidazole dissolved in the medium, the third 2 mg/L of clarithromycin, and the fourth sector 4 mg/L of amoxicillin. These antibiotic concentrations were chosen as their break point minimum inhibitory concentration values for resistance [23–26]. Inoculated plates were placed in a case where microaerophilic environment was generated (with 5% O 2 , 10% CO 2 , and 85% nitrogen) and incubated at 37 °C until colonies were seen or up to a maximum of 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…Culture plates were divided into four sectors: the first contained only the culture medium (blank), the second 8 mg/L metronidazole dissolved in the medium, the third 2 mg/L of clarithromycin, and the fourth sector 4 mg/L of amoxicillin. These antibiotic concentrations were chosen as their break point minimum inhibitory concentration values for resistance [23–26]. Inoculated plates were placed in a case where microaerophilic environment was generated (with 5% O 2 , 10% CO 2 , and 85% nitrogen) and incubated at 37 °C until colonies were seen or up to a maximum of 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…These models are valuable tools frequently utilised in evaluating the activity of antimicrobial agents used in the treatment of aerobic and anaerobic bacteria [10][11][12][13]. A three-compartment pharmacokinetic infection model was first used by Hultén et al [8] to evaluate the activity of antimicrobial agents against the intracellular organism Helicobacter pylori.…”
Section: Discussionmentioning
confidence: 99%
“…A schematic depiction of the intracellular model, which was adapted from Hultén et al [8], is shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…The activity of antibacterials against intracellular pathogens was also developed in the mid-1990s (Hulten et al 1996). A series of glass cell culture inserts containing 2-day grown monolayers of Hep-2 cells were connected to a pump with various tube diameters to simulate half-life of different drugs.…”
Section: Specialized In Vitro Kinetic Modelsmentioning
confidence: 99%